Geochemical evolution and mechanisms controlling groundwater chemistry in the transboundary Komadugu–Yobe Basin, Lake Chad region: An integrated approach of chemometric analysis and geochemical modeling - Abdulrahman Shuaibu; Robert M. Kalin; Vernon Phoenix; Ibrahim Mohammed Lawal (Journal of Hydrology: Regional Studies)
Study region: The study is conducted in the transboundary Komadugu–Yobe Basin, Lake Chad region, a critical groundwater resource shared across national boundaries of Nigeria and Niger Republic. Study focus: The research investigates geochemical evolution and sources of chemical constituents in groundwater through an integrated methodology that integrates geochemical modeling, molar ratios, bivariate plots, and chemometric analysis. Groundwater samples (n = 240) were collected during wet and dry seasons to identify seasonal variations and the impact of geogenic and anthropogenic processes on groundwater quality. New hydrological insights: The findings revealed that Cl⁻ and NO₃⁻ are associated with anthropogenic pollution. The Principal Component Analysis identified three main components associated with geogenic and anthropogenic processes, agricultural pollution, and mineral weathering. Hierarchical Cluster Analysis highlighted geogenic, anthropogenic, and evaporative influences. Groundwater in the basin is predominantly of Ca–HCO₃ and Na–Cl types and is significantly undersaturated with calcite, dolomite, and fluorite, though seasonal variations show saturation in some samples. Elevated partial pressures of CO₂ (pCO₂) above atmospheric pCO₂ in nearly all samples suggests active biogeochemical processes. Moreover, Gibbs plots, molar ratios, and bivariate plots, along with chloroalkaline indices (CAI-I & CAI-II) confirms influence of mineral weathering and ion exchange reactions within the aquifer system. Few locations show evaporation during the dry season. This study provides valuable insights for sustainable management of groundwater resources in semi-arid and arid regions.